Permanent preservation areas and legal reserve: an experience in environmental education with farming families - Streck, Morgana Taís (2013)
http://dx.doi.org/10.5902/2236117010742Permanent Preservation Areas (APPs) and Legal Reserve (RL) are areas protected by the Brazilian Forest Code that play an important role in environmental conservation. Environmental awareness activities were conducted in the Settlements Potreiro Bonito and Terra Nova, located in the City of Palmeira das Missões-RS, to promote and expand the exchange of knowledge about APP and RL, and to encourage the conservation and recovery of these areas. The mobilization of settlers for participation in activities was performed with the aid of EMATER - Palmeira das Missões and the activities consisted of lectures, questions, exchange of experiences and distribution of tree seedlings. It was observed that producers recognize the importance of preserving the APPs and RLs, however, do not feel motivated to conserve such areas, because they perceive protected areas as areas economically inactive. This dissonance between the recognition of the importance of preserving the APPs in theory, and the concern of the loss of agricultural area in practice, highlights the importance of continued investment in environmental education, primarily through projects and long-term programs, to arouse the interest of the settlers on participate directly in a production process in harmony with the environment.